Consulting report – Café Comadre - Balbina Gistel, Jasmin (2023)
This consulting report is a comprehensive analysis of Café Comadre, a coffee establishment located in Pueblo Libre, which has a dual-pronged mission of empowering Peruvian coffee farmers and promoting sustainability coffee consumption. The consulting project extensively explores various aspects of the café's operations, including its strengths, weaknesses, opportunities, and threats, shedding light on the significance of its decentralized supply network and its alignment with prevailing sustainability trends within the industry. The analysis reveals key challenges faced by Café Comadre, notably in the domains of resource management and human resources. These challenges are identified as impediments to the café's growth and sustainability objectives. To address these challenges and capitalize on its strengths, the consulting thesis offers a set of comprehensive and actionable recommendations. These recommendations encompass waste reduction strategies, leadership workshops to enhance managerial skills, forging strategic sustainability partnerships, and implementing robust customer service training programs. The thesis also underscores the imperative of fostering a culture of continuous learning within the organization. By diligently executing these strategic initiatives, Café Comadre aspires to carve a distinct and enduring niche in the highly competitive coffee market. These endeavors are meticulously aligned with the café's overarching mission and vision, which are firmly rooted in growth, sustainability, and the pursuit of operational excellence. In sum, it serves as a strategic roadmap for Café Comadre, outlining a path towards realizing its dual mission and vision, thereby reinforcing its position as a responsible and sustainable player in the dynamic coffee landscape.